NILAI KEARIFAN LOKAL TRADISI HAUL JUMAT KLIWON DI MAKAM SUNAN ABINAWA DESA PEKUNCEN KECAMATAN PEGANDON KENDAL (Sosiolium: Jurnal Pembelajaran IPS, 2023)
The background to the local wisdom value of the Haul Friday Kliwon tradition at the Sunan Abinawa Cemetery is the lack of awareness in the community about the value of this local wisdom. This usually happens due to the influence of outside culture, lack of community participation and none other than the calamity impacting the Covid-19 pandemic in Indonesia, especially in Pekuncen village so that the implementation of traditions does not work as it should. The results of the study show that the implementation of the Kliwon Friday Haul tradition at Sunan Abinawa Cemetery in 2022 is running as it should after approximately 2 years of carrying out the tradition hampered by the Covid-19 pandemic. Local wisdom values ​​were found in traditions, namely ethical values, aesthetic values, religious values ​​and social values. This value is still maintained and preserved by the community supporting the passage of the tradition. There are elements that influence the running of the Kliwon Friday Haul tradition at the Sunan Abinawa Tomb, namely community participation, economic conditions, community beliefs, and socio-culture. This element is the core thing in carrying out and preserving the Kliwon Friday Haul tradition at the Sunan Abinawa Tomb Nilai kearifan lokal tradisi Haul Jumat Kliwon di Makam Sunan Abinawa dilatar belakangi oleh kurangnya masyarakat dalam mengetahui nilai kearifan lokal tersebut. Hal ini biasanya terjadi karena pengaruh budaya luar, kurangnya partisipasi masyarakat dan tidak lain halnya musibah berdampaknya pandemi Covid-19 di Indonesia terutama di desa Pekuncen sehingga pelaksanaan tradisi tidak berjalan dengan semestinya. Hasil penelitian menunjukkan bahwa pelaksanaan tradisi Haul Jumat Kliwon di Makam Sunan Abinawa pada tahun 2022 sudah berjalan dengan semestinya setelah kurang lebih 2 tahun pelaksanaan tradisi terhambat oleh pandemi Covid-19. Ditemukan nilai kearifan lokal pada tradisi yaitu nilai etika, nilai estetika, nilai religi dan nilai sosial. Nilai tersebut sampai saat ini masih dijaga dan dilestarikan oleh masyarakat pendukung berjalannya tradisi. Terdapat unsur yang mempengaruhi bejalannya tradisi Haul Jumat Kliwon di Makam Sunan Abinawa yaitu partisipasi masyarakat, kondisi ekonomi, keyakinan masyarakat, dan sosial budaya. Unsur tersebut merupakan hal inti dalam melaksanakan dan melestarikan tradisi Haul Jumat Kliwon di Makam Sunan Abinawa.